A STUDY OF DISCOURSE MARKERS IN EFL STUDENTS’ COMPARISON AND CONTRAST TEXT - Muthmainnah Mursidin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2019)
This research was to find out: (1) the types of discourse markers used by the EFL students in comparison and contrast text and (2) the functions of discourse markers used by the EFL students in comparison and contrast text. This research employed a descriptive qualitative method. The respondents of this research was the second grade of EFL students; the total students was 30 students. The research data were collected by using an instrument namely writing activity. The writing consisted by comparison and contrast text.  The data were analyzed qualitatively. The first important finding from this research was about the types of DMs used by the students’ in three kinds of different text, there are 30 types of DMs used by the students in the comparison and compare text and the second important finding was there are four category of functions used by the students in writing activity, they were contrastive markers, inferential markers, elaborative markers, and additional subclasses markers. Despite the fact that DMs can create a smooth talk or make the conversation more natural, the students should be able to use DMs wisely in term of fluency and coherence measured in the students’ writing.